Surface acoustic cavitation understood via nanosecond electrochemistry. Part III: Shear stress in ultrasonic cleaning. - Maisonhaute, E; Prado, C; White, P; Compton, R (2002)
Acoustic cavitation is extensively used for cleaning purposes. However, little is known about the fundamental aspects of the cleaning process. Our previous electrochemical data suggested that acoustic bubbles were oscillating at a distance of only a few tens of nanometers above the surface [J. Phys. Chem. B 105 (2001) 12,087; E. Maisonhaute, B.A. Brookes, R.G. Compton, J. Phys. Chem. B 106 (2002) 3166-3172]. The flow velocities resulting from the bubble collapse lead to important drag and shear forces on the surface, responsible for cleaning and/or eroding the latter. We review here the forces acting on an adsorbed particle located on the surface, and develop arguments to explain why small adsorbates are harder to remove by sonication. Then, experimental results on particle desorption and surface effects brought about by ultrasound are presented and shown to agree with our theoretical predictions.